Psychosocial work environment and psychological strain among banking employees - Mohd. Noordin, Nurul Farhana (2015)
Psychological strain received considerable research attention in the organizational stress research. The prevalence of psychological strain at the workplace is explained by various theoretical models of psychosocial work environment such as job demand-control model, job demand-resources model, and effort-reward imbalance model. This study aims to investigate the effect of psychosocial work environment on psychological strain among employees in banking sector. In banking sector, the employees’ psychological strain is caused by unfeasible sales target, lower salaries, high workload and job insecurity. Thus, this study defines psychosocial work environment as the combination of social and psychological aspect at work. The researcher integrates the effort-reward imbalance model and the organizational justice model as the predictor of psychological strain. The target population for the present study is specifically the bank tellers in a development financial institution (DFI) and a commercial bank. The data was collected quantitatively by distributing questionnaires. This study is a preliminary study. Thus, only 150 respondents were involved in this study. The finding indicates that only reward and overcommitment significantly affect psychological strain. This finding shows the empirical evidence that the effect of psychosocial work environment on employees’ health where psychosocial work environment affects psychological strain.